A Virtual Laboratory Application for Vocational Productive Learning Using Augmented Reality - Pratama Benny Herlandy; Januar Al Amien; Pahmi Pahmi; Agus Satria (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
The objectives of this study were (1) to produce a virtual laboratory application for vocational productive learning by applying Augmented Reality technology; (2) to examine the validity of the developed application from the aspects of media development and productive learning materials. The method used in this study was research and development with the waterfall model. The stages of development included needs analysis, design, implementation, and system testing. The result of the development was the learning application called AugWare operated using an Android smartphone. The application was equipped with the features of learning materials, simulation and evaluation. The results of validation by media experts through an assessment questionnaire consisting of 32 items revealed that the average final score was 84 categorized as very appropriate. In the assessment of material experts, the results of the validator's assessment through a questionnaire with the 30 items showed that the final score was very appropriate with the score of 89.